PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WORD SQUARE UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IIIB SDN 27 PEKANBARU - Oknita Sari; Zariul Antosa; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: this research is conducted by the low of social science learning result from IIIB class of SDN 27 Pekanbaru. The KKM in the school about 75. There are 28 students in the class but only 7 students (25,00%) passed, and the other 21 students (75,00%) did not pass. With class scores 58,96. This research use Classroom Action Research, which is consisted by 2 times reguler study at class and 1 time exam. There are 28 students of SDN 27 Pekanbaru, 16 male students and 12 female students. The purpose of this research is to increase score of students grade by apply cooperative learning model of word square. The average result of this reserach at the first cycle increased to score is achieved 58,96 increasing 18,41% to be 69,82. At the second cycle the average student score have increase too about 40,52% to be 82,85. The clasical base score of social science mayor 25,00% (not passed). After cooperative learning model of word square applied in the first cycle the result increased 60,71% (still not passed) and the second cycle also increased 89,29% (passed). The teacher’s activity in first cycle was 62,50% with bad category, and increased 91,66% with very good category second cycle. The first cycle of student’s activity was 62,50% with bad category and increased 87,50% with very good category at second cycle.Key Words: word square, learning result of social science